Effect of in situ exopolysaccharide production on physicochemical, rheological, sensory, and microstructural properties of the yogurt drink ayran: An optimization study based on fermentation kinetics - Yilmaz, M. T.; Dertli, E.; Toker, O. S.; Tatlisu, N. B.; Sagdic, O.; Arici, M. (ELSEVIER SCIENCE INC, 2015)
Exopolysaccharide (EPS)-producing starter cultures are preferred for the manufacture of fermented milk products to improve rheological and technological properties. However, no clear correlation exists between EPS production and the rheological and technological properties of fermented milk products such as the yogurt drink ayran. In this study, 4 different strain conditions (EPS- and EPS+ Streptococcus thermophilus strains) were tested as a function of incubation temperature (32, 37, or 42 C) and time (2, 3, or 4 h) to determine the effect of culture type and in situ EPS production on physicochemical, rheological, sensory, and microstructural properties of ayran. Furthermore, we assessed the effect of fermentation conditions on amounts of EPS production by different EPS-producing strains during ayran production. A multifactorial design of response surface methodology was used to model linear, interaction, and quadratic effects of these variables on steady shear theological properties of ayran samples and in situ EPS production levels. The physicochemical and microbiological characteristics of ayran samples altered depending on incubation conditions and strain selection. Steady shear tests showed that ayran samples inoculated with EPS+ strains exhibited pseudoplastic flow behavior. Production of ayran with EPS- strain (control sample) resulted in the lowest apparent viscosity values (eta(50)), whereas those produced with the combination of 2 EPS+ strains yielded ayran with notably increased eta(50) values. We concluded that incubation time was the variable with the greatest effect on rho, consistency coefficient (K), and flow behavior index (n) values. In situ EPS production was also affected by these conditions during ayran fermentation in which strain-specific metabolism conditions were found to be the most important factor for EPS production. In addition, these findings correlated the amount of in situ EPS produced with the rheological properties of ayran. Scanning electron microscopy images of the samples showed differences in structural features, revealing a prominent network strand structure in the ayran samples inoculated with the admixture of 2 EPS-producing strains incubated at 37 degrees C for 3 h. These results provide useful information for large-scale production of ayran by the dairy industry.
Keywords: ayran; exopolysaccharide; rheology; optimization; STREPTOCOCCUS-THERMOPHILUS STRAINS; LACTOCOCCUS-LACTIS; STORAGE TIME; SET YOGURT; TEMPERATURE; BULGARICUS; POLYSACCHARIDE; VISCOSITY; CULTURES; TEXTURE; Agriculture; Food Science & Technology